Spinal epidural lipomatosis following bilateral spinal decompression surgery. Issue 2 (15th February 2019) - Greenish, Davyd; Watura, Karen; Harding, Ian
Abstract : A 73-year-old man underwent bilateral spinal decompression of L4/5 for severe spinal canal stenosis, requiring minimal analgesia and providing immediate relief. Two days post-operatively, he presented with new onset bilateral leg pain and difficulty mobilising. MRI demonstrated spinal epidural lipomatosis (SEL), which was not present pre-operatively, at L5/S1. Further surgery was performed with decompression of L5/S1 through removal of epidural fat. At both 3 weeks and 5 months follow-up clinics, the patient was asymptomatic. To our knowledge, this is the first case of acute spinal epidural lipomatosis directly following spinal surgery. It is important to recognise SEL as a complication following spinal surgical intervention, due to the potential development of significant neurological consequences.